SOME BIOCHEMICAL BLOOD SERUM PARAMETERS OF PREDATORY FISH DURING EUSTRONGYLIDOSIS - Honcharov, S. L. (Scientific Progress & Innovations, 2019)
The article presents the results of a study of biochemical changes in the serum of predatory fish species: pike perch – Sander lucioperca (Linnaeus, 1758), perch – Perca fluviatilis (Linnaeus, 1758) and pike – Esox lucius (Linnaeus, 1758) with estrongilidosis, which were caught in the waters of the Dnieper-Bug estuary in the delta of the Dnieper. The study was conducted in the period 2014–2018. According to our data, a decrease in the total protein content in the experimental group of perch was observed 1.36 times (p˂0.05), pikes – 1.3 times (p˂0.05), pike perch – 1.42 times (p˂0.05). The level of albumin decreased in the research group of perch 1.95 times (p˂0.05), pike – 1.4 times (p˂0.05), pike perch – 1.61 times. The content of globulins in the serum of clinically healthy and diseased fish was also different, although the differences were less significant. This indicator reached the greatest difference in the groups of pike and pike perch: the concentration of globulins decreased in the experimental groups 1.31 times (p˂0.05) (and also perch – 1.16 times (p˂0.05). The amount α-globulin serum of invaded perches was 2.2 % less (p˂0.05) less than the number of α-globulins in the perch of the control group. In the experimental group of pikes, according to our research, the number of α-globulins was significantly reduced by 7,14 % (p˂0.05), pikeperch – by 5.04 % (p˂0.05). The number of β-globulins in the blood serum of the control and experimental groups It was found that the number of serum β-globulins infested by perches increased by 7.31 % (p˂0.05), in pikes – by 6.47 % (p˂0.05) , and in pike perch – by 7.72 % (p˂0.05). The fraction of serum γ-globulins slightly increased in the research group of invaded perch by 1.32 % (p˂0.05), pike – by 4.64 % (p˂0.05), pike perch – by 3.27 % (p ˂0.05), compared to fish in the control group. An increase in the activity of AST in perches was found – by 1.31 (p˂0.05) times, pike – by 1.24 (p˂0.05), times, and in perch – by 1.45 (p˂0.05) times. In patients with perch, an increase in the activity of ALT was found to be 2.26 (p˂0.05) times, pike and zander also increased – by 3.42 and 3.17 (p˂0.05) times, respectively.